The weighted fakir miskin index as an alternative measurement of poverty: a conceptual framework / Mohd Fauzi Mohd Harun ... [et al.] - Mohd Harun, Mohd Fauzi; Abdul Rasool, Mohamaed Saladin; Mohd Salleh, Ariffin; Mohd Hanafiah, Mohd Hafiz; Idris, Noraini; Ismail, Masthurhah; Md. Taib, Ridzuan; Osman, A Gani (Universiti Teknologi MARA, Perak, 2011)
Poverty in Malaysia is commonly conceptualized from the perspective of monetary or income. Economists have argued that the current monetary approach is not able to reflect the multidimensional nature of poverty which has developed due to the rapid economic development process via globalization and liberations of trade and businesses. This paper proposes a multidimensional poverty measurement using index. The proposed method via the Weighted Fakir Miskin Index comprising of nine components is expected to capture a more realistic poverty group. Furthermore, the multidimensional phenomenon of poverty in a more holistic way is envisaged to be captured and is expected to have an impact to the policy makers as it gives a new perspective of measuring poverty.